Induction of CX3CL1 expression by LPS and its impact on invasion and migration in oral squamous cell carcinoma - He, Chanjuan; Wu, Yuehan; Nan, Xiaoxu; Zhang, Weifang; Luo, Yu; Wang, Honglan; Li, Mengqi; Liu, Changyue; Liu, Jiaming; Mou, Xuelin; Liu, Ying (Frontiers in Cell and Developmental Biology, 2024)
Purpose: This study aimed to explore the expression of CX3CL1 induced by lipopolysaccharide (LPS) in oral squamous cell carcinoma (OSCC) and its impact on biological characteristics such as invasion and migration, taking the foundation for new targets for the treatment and prognosis of OSCC. Methods: This study utilized a variety of techniques, including bioinformatics, molecular biology, and cell experiments, to investigate the expression of CX3CL1 and its receptor CX3CR1 in OSCC patients’ cancer tissues or OSCC cell lines. Extracting, organizing, and analyzing the TCGA database on the expression of CX3CL1 and its receptor CX3CR1 in cancer tissues and corresponding paracancerous normal tissues of OSCC patients by bioinformatics methods. The expression of CX3CL1 in cancerous and normal tissues of OSCC patients was verified by IHC, and the changes in mRNA and protein expression of CX3CL1 and its receptor CX3CR1 in OSCC cell lines were detected before and after lipopolysaccharide LPS stimulation by RT-PCR, ELISA, and WB. Changes in cell biological behavior by overexpression of CX3CL1 in OSCC cell lines were detected by CCK-8, Transwell, scratch healing assay, and cloning assay. The effects of overexpressing cell lines on the AKT pathway and Epithelial-mesenchymal Transition (EMT)-related protein expression before and after LPS stimulation were detected by Western Blot. Results: (1) CX3CL1 and its receptor CX3CR1 were found to be downregulated in OSCC tissues of patients or OSCC cell lines. (2) After LPS stimulation, CX3CL1 gene expression increased in both OSCC cell lines, while CX3CR1 expression remained unchanged. (3) OSCC cell lines overexpressing CX3CL1 showed changes in cell biological characteristics, including decreased proliferation, invasion, migration, and stemness, which were more pronounced after LPS stimulation. (4) Overexpression of CX3CL1 in OSCC cell lines decreased EMT-related protein expression and AKT phosphorylation. On the contrary were promoted by LPS stimulation. Conclusion:CX3CL1 and CX3CR1 are downregulated in OSCC cancer tissues and cell lines compared to adjacent normal tissues and cells. LPS stimulation increases CX3CL1 expression in OSCC cell lines, suggesting that inflammation may induce CX3CL1 expression and that the CX3CL1 gene may play an important role in OSCC progression. Overexpression of CX3CL1 inhibits OSCC cell proliferation, migration, invasion, and stemness, suggesting that CX3CL1 plays a critical role in suppressing OSCC development. CX3CL1 suppresses OSCC invasion and migration by affecting EMT progression and AKT phosphorylation, and partially reverse the process that LPS causes and affects the development of OSCC.